Acquisition of mathematical concepts by elementary school boys' students (Journal of the College of Basic Education, 2022)
The current research aims to identify the acquisition of mathematical concepts by elementary school boys' students. The descriptive survey method was adopted for the research. The research sample consisted of (300) male students of the sixth grade of primary school, For the General Directorates of Education in Baghdad / Rusafa (the first, the second, the third) and Karkh (the first, the second, and the third), They were randomly selected for the second semester of the year (2021 - 2022)A.D . And then preparing the research tool, which is : Test the acquisition of mathematical concepts at three levels for each concept (defining the concept, distinguishing the concept, applying the concept), It consists of (78) topical paragraphs (multiple choice) with (26) main concepts, and each concept has three paragraphs for levels of concept acquisition. Using the alpha-Cronbach equation, it was found that the value of the reliability coefficient of the test was (0.863). The results showed a low percentage of acquiring mathematical concepts for boys in the primary stage in general, Where the percentage of boys acquiring total concepts reached (10.41%), which is equivalent to (31) students who acquired mathematical concepts, The percentage of students of the General Directorate of Rusafa Education for boys acquiring holistic concepts was (9.77%), which is equivalent to (3) students who acquired mathematical concepts, The percentage of students of the General Directorate of Rusafa Education for boys acquiring holistic concepts reached (12.54%), which is equivalent to (3) students who acquired mathematical concepts, The percentage of students of the General Directorate of Education of Rusafa acquiring the third of the overall concepts was (10%), which is equivalent to (3) students who acquired mathematical concepts. The percentage of acquiring holistic concepts by the General Directorate of Karkh Education for Boys’ students is (14.15%), which is equivalent to (7) students who have acquired mathematical concepts. While the percentage of students of the General Directorate of Education in both Al-Karkh Second and the Third Karkh acquiring total concepts was equal, as it reached (8%), which is equivalent to (4) students in each of the two directorates who acquired mathematical concepts. Several recommendations were reached, the most important of which is the diversity of teaching methods and methods used in the presentation of educational content that develop the desires of boys' students and lead to attracting their attention and increasing their interaction, participation and motivation towards learning and their acquisition of mathematics.